Protective effects of seed oil from Nicotiana tabacum L. On D-galactose induced liver and brain damages of mice by regulating PI3K/Akt/Nrf2 signaling pathway - Ji Gu; Yongchao Wang; Shanshan Xiao; Yunye Zheng; Zhengxuan Wang; Yaping Liu; Limeng Zhang; Guiguang Cheng (Journal of Functional Foods)
Nicotiana tabacum L. seed oil is rich in unsaturated fatty acids and has potential applications in functional or nutritional foods. The present study aimed to investigate the protective effects of Nicotiana tabacum L. seed oil (NC89 and BS4) against D-galactose (D-gal) -induced brain damage in aging mice and the potential molecular mechanisms. Combined with GC/MS component analysis and network pharmacology prediction, the aging related PI3K/Akt/Nrf2 pathway was found for further verification. Histopathological results showed that NC89 and BS4 could significantly improve the cellular damage of liver, brain, kidney and heart tissues in D-gal-induced aging mice. NC89 and BS4 exerted antioxidant capacity by increasing the activities of SOD, CAT, GSH-Px and T-AOC in serum, liver and brain tissues, and reducing the accumulation of MDA in plasma. In addition, NC89 and BS4 also reduced the contents of serum TNF-α and IL-6, showing an anti-inflammatory effect. Notably, NC89 and BS4 protect cranial nerves by increasing AChe activity in the brain. Western blotting results showed that NC89 and BS4 increased the ratios of p-PI3K/PI3K and p-Akt/Akt, as well as the protein expression of Nrf2, NQO1 and HO-1 in brain tissues. Therefore, the potential protective mechanism of NC89 and BS4 on the liver and brain may be related to the activation of the PI3K/Akt/Nrf2 pathway and the inhibition of inflammatory responses. This study provides new insights into the biological activities of NC89 and BS4.